IMPLEMENTATION OF CEDAW DUE TO HUMAN RIGHT AND EDUCATION DISCRIMINATION REGARDING DALIT WOMAN IN INDIA - Febri D. Hasibuan; Rizky Annisa Sabrina (Emerald: Journal of Economics and Social Sciences, 2023)
The focus of this research it to understand the problem in implementing the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW) due to human right and education discrimination regarding Dalit woman in India. This research is using International Law, Human security and human right education concept to analyze the problem. Qualitative method is chosen to accommodate a more understanding of the social phenomena rather than numbers. Data are collected through literature review from a vary resource. The finding of this research is that India society interacted in hierarchies. Historically, the Hindu caste is divided into four categories, but there is still the lowest caste level, known as Dalit. Discrimination of Dalit’s is normally practice because they are considered a group that does not have Varma. Dalit’s are often subjected to inhumane treatment, even being excluded from everyday life including the right to have education. The majority of Dalit women have experienced one or more incidents of violence, such as verbal abuse, physical assault, sexual harassment, rape, and domestic violence. The implementation of CEDAW in India is not the main reference in its national law. This is because there are several articles that are reserved by the Indian government, even though it has been ratified and included as international law.